Rancang Bangun Aplikasi Kasir Berbasis Web Menggunakan Library ReactJS dan Framework ExpressJS: (Studi Kasus Toko Haii Shoes Kendal) - Muhammad Malfin; Bagus Sudirman; Ahmad Ashifuddin Aqham (Jurnal Informatika Dan Tekonologi Komputer (JITEK), 2026)
The purpose of this research is to design and build a web-based cashier application to solve the problems of transaction recording, report generation, and inventory management of product size variants which are still done manually using bookkeeping and Microsoft Excel at the Haii Shoes Kendal Store. The software development method used in this research is the Software Development Life Cycle (SDLC) with a Waterfall model approach. According to the development specifications, the software used to build this system includes the ReactJS library on the client-side interface (frontend), the ExpressJS framework on the server-side system (backend), Prisma ORM with the MySQL database management system, and Postman for API service testing. The analysis results of this study indicate that the built system has successfully automated sales recording (real-time), provided inventory management features along with their size variants precisely, and presented sales and profit recapitulation reports that can be exported. Based on the test results using the Black Box method and validation from end-users, all system functionalities have operated very well following the operational needs of the store.